Second Career Readiness After Retirement: Self-Efficacy, Positive Expectations, and Clear Goal Aspect - Muhammad Zulfikar; Muhammad Alridho Lubis; Nurhasanah Harahap; Berru Amalianita (Kuras Institute, 2026)
This study aims to analyze the readiness of second careers after retirement among members of the Juang Kencana Community of Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) Jambi Province. Using a mixed-methods approach with concurrent design, quantitative data were collected from 31 retirees through questionnaires, while qualitative data were obtained through in-depth interviews with key informants. The findings reveal that overall, second career readiness is in the high category, with 58.06% of participants demonstrating strong self-efficacy, positive expectations, and clear goals. Self-efficacy emerged as the strongest aspect (70.97% high), followed by outcome expectations (61.29% high), while goals were relatively weaker (54.84% high). Qualitative findings support this by showing that retirees who remain engaged in entrepreneurial or organizational activities feel healthier, more motivated, and socially supported, although challenges such as declining business income, limited participation of community leaders, and irregular activity implementation persist. The novelty of this study lies in its integration of quantitative indicators and qualitative insights, highlighting the importance of family support, community involvement, and organizational platforms in strengthening second career readiness. The implications suggest that policymakers and community organizations should design programs that not only provide economic opportunities but also foster mental resilience and social engagement for retirees, ensuring their continued contribution to society.